Antiphospholipid Antibodies: Prevalence, Clinical Significance and Correlation to Cytokine Levels in Acute Myeloid Leukemia and Non-Hodgkin’s Lymphoma - Stasi, Roberto; Stipa, Elisa; Masi, Mario; Oliva, Felicia; Sciarra, Alessandro; Perrotti, Alessio; Zaccari, Giuseppe; Papa, Giuseppe (Thrombosis and Haemostasis, 1993)
This study was designed to explore the prevalence and clinical significance of elevated antiphospholipid antibodies (APA) titres in patients affected by acute myeloid leukemia (AML) and highgrade non-Hodgkin’s lymphoma (NHL). We also analyzed possible correlations with circulating levels of interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-alpha), and the soluble form of the receptor for interleukin-2 (sIL-2r). Nineteen patients with de novo AML and 14 patients with newly-diagnosed NHL were investigated. Tests for APA included the measurement of anticardiolipin antibodies (ACA) with a solid-phase immunoassay, and the detection of the lupus-like anticoagulant (LA) activity. Five patients with AML (26.3%) and 5 patients with NHL (35.7%) presented elevated APA at diagnosis, as compared to 3 of 174 persons of the control group (p <0.0001). APA titres became normal in all patients responding to treatment, whereas nonresponders retained elevated levels. In addition, 6 patients (4 with AML and 2 with NHL), who had normal APA at diagnosis and were either refractory to treatment or in relapse, subsequently developed LA and/or ACA positivity. At presentation, the mean levels of IgG- and IgM-ACA in patients were not significantly different from Controls, and concordance between ACA and LA results reached just 30%. With regard to the clinical course, we were not able to detect any statistically significant difference between patients with normal and elevated APA. Pretreatment concentrations of IL-6 and TNF-alpha in AML, and sIL-2r in NHL were found significantly elevated compared to Controls (p = 0.003, p = 0.009 and p = 0.024 respectively). In addition, the levels of these cytokines correlated with IgG-ACA at the different times of laboratory investigations. These results demonstrate that APA may have a role as markers of disease activity and progression in some haematological malignancies.